Validity and reliability of the Food-Life Questionnaire. Short form - Sharp, Gemma; Hutchinson, A.; Prichard, I.; Wilson, C. (Elsevier BV, 2013)
Measures of beliefs and attitudes towards food need to be valid, and easy to use and interpret. The present study aimed to establish the validity and reliability of a short-form of the Food-Life Questionnaire (FLQ). Participants (247 females; 118 males), recruited in South Australia, completed a questionnaire in 2012 incorporating the original FLQ, a revised short form (FLQ-SF), and measures of food choice and consumption. Validity (construct, criterion-related, and incremental) and reliability (internal consistency and short-form) were assessed. Factor analysis established that short-form items loaded onto five factors consistent with the original FLQ and explained 60% of variance. Moderate correlations were observed between the FLQ-SF and a measure of food choices (r = .32–.64), and the FLQ-SF predicted unhealthy food consumption over and above the full FLQ demonstrating criterion-related and incremental validity respectively. The final FLQ-SF included 21 items and had a Cronbach’s alpha of .75. Short-form reliability was established with correlations between corresponding subscales of the FLQ and FLQ-SF ranging from r = .64–.84. Overall, the FLQ-SF is brief, psychometrically robust, and easy to administer. It should be considered an important tool in research informing public policies and programs that aim to improve food choices.